Educação permanente em saúde na assistência obstétrica para implementação da rede cegonha - Silva, Fernanda Lima e (2016)
Permanent Health Education is an important tool for the health team in obstetric assistance and in this sense, offers elements to guide the process of training of professionals who work on attention(care) to the woman on Maternity Support Network. This study aimed to analyze the Permanent Health Education care in obstetric assistance for implementation of the Maternity Support Network. This is an exploratory-descriptive research with qualitative approach conducted with nurses from two public maternity in Goiânia-Goiás. The data collection occurred through semi-structured individual interviews and analysis took place by content analysis with the aid of the Atlas ti version 7. With the analysis of discourses emerged four categories: 1) Permanent Health Education, in which the subjects reported the understanding of the term in question and mentioned the strategies used in the service. 2) Permanent Health Education - factors that interfere, in which were the factors that hinder the implementation of permanent health education of activities in assisting the woman in the gravid-puerperal period. 3) challenges in implementing the maternity support network, in this category the participants spoke about the difficulties in practice what the maternity support network advocates. 4) contributions of permanent health education for implementation of maternity support network, which gathered the data concerning the importance of permanent health education. The results pointed to the importance of permanent health education as a strategy to address the challenges in the implementation of the maternity support Network, however are necessary investments in the training of professionals with management awareness, encouragement and provision of professional employees in satisfactory amount.